Exploring Teachers’ Perceptions Toward the Integration of AI Tools in the Language Classroom - Kalra, Rusma (NIDA Journal of Language and Communication, 2025)
This research investigates English instructors’ perceptions of the benefits and challenges associated with the integration of AI application tools into an English classroom at an international university in Thailand. Two primary research questions guide the study: (1) How do English instructors perceive the benefits of AI application tools? and (2) How do they perceive the challenges of integrating AI tools? The research mainly adopts a quantitative approach, utilizing a structured survey questionnaire developed based on existing literature. Additionally, semi-structured interviews with 20 randomly selected instructors provide qualitative insights. The findings indicate widespread adoption of AI-powered tools among instructors teaching English at this international university. Notably, language learning applications are the most utilized and the most notable challenge identified by participants is the apprehension that learners may develop excessive reliance on AI tools. This research provides comprehensive insights into perceptions surrounding the integration of AI application tools in English language classrooms at an international university in Thailand. These insights contribute to a deeper understanding of the benefits and challenges associated with AI tools in educational settings.